Generalized tonic-clonic seizures as the initial symptom of late-onset Krabbe disease: a Case Report - Xie, Sifen; Kuang, Zuying; Pan, Mengqiu; Zhang, Kanghua; Ye, Jinlong; Li, Bo; Luo, Sheng; Wang, Zhanhang (Frontiers in Behavioral Neuroscience, 2025)
Krabbe disease (KD), also known as globoid cell leukodystrophy, is a rare autosomal recessive neurodegenerative disorder caused by pathogenic variants in the GALC gene. While infantile-onset KD is prevalent globally, adult-onset KD is frequently presented in East Asian populations and typically manifests with progressive spastic paraparesis. We herein report a unique case of a 28-years-old male who initially presented with generalized tonic-clonic seizures, rather than the classic gait disturbance. Brain MRI revealed symmetrical white matter lesions and early cortical involvement. Genetic testing revealed compound heterozygous GALC variants (c.908C > T/p.Ser303Phe and c.136G > T/p.Asp46Tyr). Subsequent enzyme assays confirmed low galactocerebrosidase activity. This case broadens the clinical spectrum of adult-onset KD and highlights the importance of considering KD in the differential diagnosis of adult epilepsy with progressive neurological symptoms.